2010
DOI: 10.1111/j.1442-2042.2010.02584.x
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance intravesical bacillus Calmette‐Guérin instillation for Ta, T1 cancer and carcinoma in situ of the bladder: Randomized controlled trial by the BCG Tokyo Strain Study Group

Abstract: Objectives:We carried out a prospective, randomized , controlled trial to investigate the efficacy and safety of both induction and maintenance therapy with intravesical instillation of bacillus Calmette-Guérin (BCG) for high-risk non-muscle invasive bladder cancer (NMIBC). Methods: Intravesical instillation of 80 mg Tokyo strain was given to patients with high-risk NMIBC, including carcinoma in situ (CIS), once weekly for eight consecutive weeks as induction therapy. Patients who achieved complete response (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 12 publications
4
57
0
1
Order By: Relevance
“…The patients were followed up every 3 months during the first 2 years, and every 6 months thereafter (14). End-points were RFS and progression-free survival (PFS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients were followed up every 3 months during the first 2 years, and every 6 months thereafter (14). End-points were RFS and progression-free survival (PFS).…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion criteria were high-risk NMIBC and recurrent NMIBC, such as, pathologically confirmed Ta, T1 and CIS of the bladder, administration of intravesical initiation or maintenance immunotherapy, performance status of 0-2, ability to undergo cystoscopy and TUR-BT, and intact function of main organs (14). Exclusion criteria included reduced dosage of BCG Tice strain, failure of consecutive treatment, strongly positive tuberculin test, history of intravesical BCG instillation, severe bladder irritation before the start of BCG administration and active serious medical complications.…”
Section: Methodsmentioning
confidence: 99%
“…Saint et al (17) similarly demonstrated that the maintenance therapy reported on by Lamm et al (6) for NMIC yielded a significant reduction in recurrence, but adherence was hindered by adverse reactions: 81% of the patients discontinued the treatment. In Koga et al (18), the number of maintenance instillations was set at four. Maintenance consisting of just four instillations decreased the recurrence rate, compared with induction alone, although this study failed to show significant superiority of the four-instillation maintenance schedule without serious adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…13 Five RCTs com pared non3week maintenance schedules to BCG induction only (Table 1). [14][15][16][17][18] None of these alternative maintenance schedules showed a statistically significant reduction in recurrence (range -4% to 22%, average 7%). By contrast, two studies that compared 3week mainten ance to induction treatment alone showed a statistically significant 28% reduction in tumour recur rence (Table 2).…”
Section: Optimal Schedule and Duration Of Therapymentioning
confidence: 99%